Program Kampus Merdeka: Wadah Mahasiswa Berkreasi, Berinovasi, dan Berprestasi - Intan Defi Anggini; Masduki Asbari; Septiana Permata Noor (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study is to find out one of the programs from Merdeka Campus, namely the Certified Independent Internship and Study Program (MSIB) to Create a Container for Students to Create, Innovate, and Achieve. In this Study Report, it uses a descriptive qualitative method by listening to notes because the data sources are obtained by listening to oral narratives from the Directorate General of Diktiristek's Youtube channel entitled